The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10162-008-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Intracochlear Sound Pressure Measurements in Normal Human Temporal Bones

Abstract: We present the first simultaneous sound pressure measurements in scala vestibuli and scala tympani of the cochlea in human cadaveric temporal bones. The technique we employ, which exploits microscale fiberoptic pressure sensors, enables the study of differential sound pressure at the cochlear base. This differential pressure is the input to the cochlear partition, driving cochlear waves and auditory transduction. In our results, the sound pressure in scala vestibuli (P SV ) was much greater than scala tympani … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
235
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(275 citation statements)
references
References 27 publications
39
235
1
Order By: Relevance
“…The model results were compared with the experimental data measured in human temporal bones by several groups. Middle-ear sound pressure gain reached the maximum value at frequencies of 1 -2 kHz predicted by the FE model and measured in temporal bones by Aibara et al (2001), Nakajima et al (2009) and Puria and Allen (1991). The good agreement between the model-predicted middle-ear transfer function and that measured in human temporal bones in acoustic pressure transmission is shown in Figure 6.…”
Section: Comparison Of Model With Published Datasupporting
confidence: 57%
See 2 more Smart Citations
“…The model results were compared with the experimental data measured in human temporal bones by several groups. Middle-ear sound pressure gain reached the maximum value at frequencies of 1 -2 kHz predicted by the FE model and measured in temporal bones by Aibara et al (2001), Nakajima et al (2009) and Puria and Allen (1991). The good agreement between the model-predicted middle-ear transfer function and that measured in human temporal bones in acoustic pressure transmission is shown in Figure 6.…”
Section: Comparison Of Model With Published Datasupporting
confidence: 57%
“…As shown in Figure 6(A), the pressure gain from the TM to the SV has a maximum magnitude of approximately 23 dB. The FE model well predicted the middle-ear pressure gain over frequencies of 0.2-8 kHz compared to the results measured from human cadaver ears by Aibara et al and Puria et al The magnitude curve of model was about 4 dB higher than the results reported by Nakajima et al (2009) above 1 kHz.…”
Section: Model Validationsupporting
confidence: 45%
See 1 more Smart Citation
“…methods used to measure ear-canal pressure and velocities (e.g., stapes, round window, promontory, etc.) have been described in earlier publications [1,3]. The cartilaginous ear canal was removed in our preparation, thus the contribution of ear canal compression (occusion effect) of BC that would have occurred was presumably reduced in these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Because the highest voltage before significant distortion occurred was approximately 71 mV RMS , an input voltage of about 40 mV RMS across all frequencies was used. Intracochlear pressure measurements were made using 150-160 m diameter fiberoptic pressure sensors developed by Olson [1]. Cochleostomies (~200 m in diameter) were drilled by hand under fluid to prevent entrance of air into the cochlea.…”
Section: Introductionmentioning
confidence: 99%